Characterization of gene expression patterns in response to an orthotospovirus infection between two diploid peanut species and their hybrid - Chen, Yi-Ju; Catto, Michael A.; Pandey, Sudeep; Leal-Bertioli, Soraya; Abney, Mark; Hunt, Brendan G.; Bag, Sudeep; Culbreath, Albert; Srinivasan, Rajagopalbabu (Frontiers in Plant Science, 2023)
Tomato spotted wilt orthotospovirus (TSWV) transmitted by thrips causes significant yield loss in peanut (Arachis hypogaea L.) production. Use of peanut cultivars with moderate field resistance has been critical for TSWV management. However, current TSWV resistance is often not adequate, and the availability of sources of tetraploid resistance to TSWV is very limited. Allotetraploids derived by crossing wild diploid species could help introgress alleles that confer TSWV resistance into cultivated peanut. Thrips-mediated TSWV screening identified two diploids and their allotetraploid possessing the AA, BB, and AABB genomes Arachis stenosperma V10309, Arachis valida GK30011, and [A. stenosperma × A. valida] 4x (ValSten1), respectively. These genotypes had reduced TSWV infection and accumulation in comparison with peanut of pure cultivated pedigree. Transcriptomes from TSWV-infected and non-infected samples from A. stenosperma, A. valida, and ValSten1 were assembled, and differentially expressed genes (DEGs) following TSWV infection were assessed. There were 3,196, 8,380, and 1,312 significant DEGs in A. stenosperma, A. valida, and ValSten1, respectively. A higher proportion of genes decreased in expression following TSWV infection for A. stenosperma and ValSten1, whereas a higher proportion of genes increased in expression following infection in A. valida. The number of DEGs previously annotated as defense-related in relation to abiotic and biotic stress was highest in A. valida followed by ValSten1 and A. stenosperma. Plant phytohormone and photosynthesis genes also were differentially expressed in greater numbers in A. valida followed by ValSten1 and A. stenosperma, with over half of those exhibiting decreases in expression.